An Overview of The Psychological Well-Being Of Entrepreneurs In Riau Province - Sri Maryatmi Anastasia; Yudi Hardiyanto (Research Synergy Foundation, 2022)
At this time when competition in the economy is increasing and the COVID-19 pandemic situation, not all entrepreneurs in entrepreneurship are able to reach the level of psychological well-being because no one can guarantee whether the business will be successful or not. This study aims to give the description of psychological well-being on entrepreneurs in Riau Province during the COVID-19 pandemic and to determine the differences on psychological well-being among entrepreneurs in Riau Province base on the demographic data of entrepreneurs. The method used to collect the data of psychological well-being and a demographic scale is distribute the questioners to 130 entrepreneurs in Riau Province. The sampling technique used is cluster random sampling. The analytical method used is descriptive analysis and different test using program SPSS 23.0. Based on the analysis test, it was found that the level of psychological well-being in entrepreneurs in Riau Province was classified as moderate. The dimensions of self-acceptance, positive relationships with others, autonomy, purpose in life and environmental mastery in entrepreneurship in Riau Province are moderate, while the dimensions of personal growth in entrepreneurship in Riau Province are high. The results also show that the hypothesis is rejected with no significant difference in the psychological well- being of Riau Province entrepreneurs based on the demographic factors tested.